2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7318391
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of accuracy and reliability of PulseOn optical heart rate monitoring device

Abstract: PulseOn is a wrist-worn optical heart rate (HR) monitor based on photoplethysmography. It utilizes multi-wavelength technology and optimized sensor geometry to monitor blood flow at different depths of skin tissue, and it dynamically adapts to an optimal measurement depth in different conditions. Movement artefacts are reduced by adaptive movement-cancellation algorithms and optimized mechanics, which stabilize the sensor-to-skin contact. In this paper, we evaluated the accuracy and reliability of PulseOn tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 6 publications
2
30
0
Order By: Relevance
“…1b, c, ▶table 1). In the absence of dedicated tools to assess this imprecision, we can only assume that this was due to motion artifacts from the arm and chest movements, as reported by others [12,14,16]. As a corollary, these three sports also provided the widest LOAs, yet still less than those of the same brand wrist-worn model [14].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…1b, c, ▶table 1). In the absence of dedicated tools to assess this imprecision, we can only assume that this was due to motion artifacts from the arm and chest movements, as reported by others [12,14,16]. As a corollary, these three sports also provided the widest LOAs, yet still less than those of the same brand wrist-worn model [14].…”
Section: Discussionmentioning
confidence: 87%
“…The HR values of OHR are insufficiently accurate [9][10][11][12][13], despite recent improvements in the number of usable light emitters and the built-in algorithms [14,15]. Among the many reasons are mainly low skin temperature [16], motion artifacts [16,17], inadequate attachment or positioning [13,16,18], skin type [14,15], activity type [19] and intensity of exercise [9,19,20]. Another reason is the number of LED sources: most brands use two or three light sources, which may be insufficient to retrieve blood flow data, especially through the bony wrist region, more sensitive to motion artifacts [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparing the instant heart rate calculated from ECG and the instant pulse rate calculated from the prototype device, we used resampled values at 1 Hz by linear interpolation for each. Furthermore, in performing a quantitative evaluation of the accuracy of detecting heart rate variability, we defined reliability and accuracy as follows (Delgado-Gonzalo, 2014).…”
Section: Laboratory Protocol and Evaluationmentioning
confidence: 99%
“…Validation studies have been done to evaluate accuracy of HR, EE and other measurements in healthy subjects for a variety of fitness trackers [5][6][7][8][9][10][11][12][13][14][15][16][17]. Boudreaux et al [7] tested eight devices for accuracy of HR and EE measurements on healthy subjects and found that HR accuracy from wearable devices differed at different exercise intensities with an increasing underestimation of HR at higher exercise intensities.…”
Section: Introductionmentioning
confidence: 99%